ANALISIS PENGARUH FAKTOR HYGIENE DAN FAKTOR MOTIVATOR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT KARYA GUNA EKATAMA - Yohana Fransiska Nirmalasari (Ma Chung Press, 2018)
One of the efforts undertaken by the company to improve the quality of human resources is to consider the job satisfaction of employees. when an employee satisfaction in the work that an employee will do everything to complete the task, which will produce a good performance and achievement for the company. In this study will discuss the factors that may affect job satisfaction using the object of research at PT Karya Guna Ekatama. The purpose of this research is to analyze the hygiene factors and motivational factors that influence job satisfaction and factors determine a bigger factor to job satisfaction. In this study, researchers used Herzberg's theory of motivation someone who saw into 2 factors, hygiene factors and motivational factors. Both of these factors will be the independent variable in this study with the dependent variable is job satisfaction. The research method in this study using multiple linear regression to determine the influence of the independent variable on the dependent variable. The results obtained are both factors have an influence on employee job satisfaction, but of the two factors that most influence on employee job satisfaction is the motivating factor. The conclusions obtained that the hygiene factors and motivational factors affect the job satisfaction and motivational factors have a greater influence on job satisfaction